Regulation of actin cytoskeleton dynamics by Arf-family GTPases - Myers, Kenneth R. (2008)
Small GTPases of the Arf family are best known for their role in vesicular transport, wherein they nucleate the assembly of coat proteins at sites of carrier vesicle formation. However, accumulating evidence indicates that the Arfs are also important regulators of actin cytoskeleton dynamics and are involved in a variety of actin-based processes, including cell adhesion, migration and neurite outgrowth. The mechanisms of this regulation are remarkably diverse, ranging from the integration of vesicular transport with cytoskeleton assembly to the direct regulation of Rho-family GTPase function. Here, we review recent progress in our understanding of how Arfs and their interacting proteins function to integrate membrane and cytoskeletal dynamics.